Micromorphology of the upper anthecium in Mesosetum Steud. and related genera (Poaceae, Arthropogoninae) and its taxonomic applications - Silva, Anádria Stéphanie da (2015)
Mesosetum is a Neotropical genus with 25 species, and 21 of them occur in Brazil. Mesosetum forms a clade closely related with Keratochlaena rigidifolia and Tatianyx arnacites. The objective of this work was to establish the taxonomic value of the upper anthecium micromorphology for the group. A total of 96 specimens, representing all Mesosetum species (except M. wrightii), K. rigidifolia and T. arnacites were examined under a scanning electron microscope (SEM). PCA and UPGMA analysis were applied using the micromorphologicalcharacters. Fifithteen useful taxonomic characters were identified. We highlight the following characters to distinguish the Mesosetum species: the presence, type and distribution of papillae on the abaxial surface of the upper lemma; the presence of unicellular macrohairs and bicellular microhairs; presence or absence of silica cells and the structure of the germination lid. The present work shows that the micromorphological characters identified are important taxonomically at the specific level, allowing the species identification in many cases.